The book of Sarah - Lightman, Sarah 1975- (Myriad Editions, 2019)
"There is no Book of Sarah in the Bible, so artist Sarah Lightman sets out to make her own. In this quietly subversive graphic autobiography, Lightman follows the urge to find herself in the midst of training to become an artist, observing her faith, navigating family and romantic relationships, and learning to be a mother."--Source of summary unspecified